Meta-avaliação do sistema de avaliação institucional da escola técnica estadual parque da juventude do Centro Paula Souza - Perez, Marinês Oliveira (2014)
The theme of the study has emerged from the observation of the meta-evaluation process developed by the working team of the Institutional Evaluation System from Parque da Juventude Technical School, especially concerning the results obtained and the improvements that have been developed by the teachers, students, parents and community. Questioning the institutional evaluation means reflecting on your effectiveness as a process as well as its administrative effectiveness. The institutional evaluation being the major axis of management, control method and organization of the actions of school administrators, understanding how it is done and the importance that it has in school management becomes so relevant as necessary. In this way, experiencing this system from its objectivity and results shown for management decision leading us to think carefully about the necessity to evaluate the system. It means: meta-evaluation. The meta-evaluation was established as a mechanism for evaluating its own evaluations. Concerning this initial understanding, the research investigation focused to analyze the Institutional Evaluation System (SAI) of the Technology Education Center Paula Souza (CEETEPS) from Parque da Juventude Technical School (ETEC) as the concepts , practices and perspectives of the institutional evaluation in this context. The theoretical and empirical research was developed through exploratory, qualitative research, adopting a case report focused on the CEETEPS/ ETEC and SAI. In this way, the data collection was conducted through bibliographic and documentary research methodologies and semi-structured questionnaire with open questions, with the social subjects that make up the Evaluation Committee (Working Team) responsible for the meta-evaluation of the SAI/CEETEPS /ETEC Parque da Juventude. The results showed deficient levels in evaluative reports that, given the change of the evaluation system, it was devoid of any planning and/or action for improvement as well as the unfamiliarity of evaluation management team that will be and how it should conduct a meta-evaluation. Due to the displayed results, this study suggests the improvement of the evaluation management team, regarding the evaluation processes and meta-evaluation, as well as the prior establishment of action plans that consider the continuous improvement of the indicators reviewed and not only, specific and emergencial plans that aim to solve deficiencies identified in the evaluation reports.